Analisis Kinerja Simpang Tiga Tak Bersinyal (Studi Kasus: Jalan Karyawiguna - Jalan Akordion Barat - Jalan Sasando, Tunggulwulung, Loakwaru, Kota Malang) - Pajangga , Indra Habaita; Arifianto , Andy Kristafi; Yurnalisdel, Yurnalisdel (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Malang City has a dense population and affects vehicle mobility on the road, especially the intersection analyzed in this study is Jalan Karyawiguna-Jalan Akordion Barat-Jalan Sasando, Tunggulwulung, Lowokwaru, Malang City. At local road intersections without traffic signals, this often results in delays, queues and traffic jams. Fuel is wasted in traffic jams, which also contribute to air pollution, noise, and slowed movement of goods and services. This research method uses deductive-inductive qualitative research methodology. the research uses descriptive research type and determines the location. The results of the research found data in the field such as traffic volume surveys conducted using the average traffic survey method (LHR). The results of the study for 1 week the highest peak hour volume = 3024 skr / hour, capacity (C) = 2282 skr / hour, degree of saturation (DJ) = 1,3, exceeding the standard DJ value set in PKJI (DJ ˂ 0,85). Therefore, the traffic volume at this intersection is classified as level of service F (Very high) and has unstable flow characteristics.